Analisis Penerapan Sistem Keuangan Desa (Siskeudes) Dalam Pengelolaan Keuangan Pendapatan Dan Belanja Desa (APBDES) Di Desa Kecamatan Pupuan Kabupaten Tabanan. - Sumarliati, Ni Putu; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2025)
The village financial system is a very crucial part of good village governance. With a well-organized, transparent, and accountable financial system, villages can manage village budgets and funds more effectively for the welfare of the community. This study aims to determine the application of the village financial system (Siskeudes) in the management of village income and expenditure finances (APBDES) in Pupuan District Village, Tabanan Regency. Data collection was carried out by conducting interviews with several sources. The data analysis steps were carried out by collecting data, analyzing data which can then be concluded. From the results of the analysis that has been carried out, it can be seen that most villages in Pupuan District use the village financial system to manage the village income and expenditure budget (APBDes). The obstacles faced by Pupuan District villages in implementing the authority to manage village finances are the minimal capacity of the apparatus, relatively narrow planning time, lack of village institution functions, and low participation of the community, government apparatus.